Effect of mindfulness on anxiety and depression in insomnia patients: A systematic review and meta-analysis - Li, Hangyu; Qin, Wanli; Li, Nannan; Feng, Shixing; Wang, Junqi; Zhang, Yuan; Wang, Tianyi; Wang, Chenlu; Cai, Xuanyi; Sun, Wen; Song, Yang; Han, Dongran; et al. (Frontiers in Psychiatry, 2023)
Background As a common clinical symptom, insomnia has a high incidence of combined mental illness and it is also a risk factor for the development of depression, anxiety and suicide. As a new concept in the field of health in recent years, mindfulness therapy can improve insomnia, anxiety and depression, which is a new way to solve such diseases. Objective This study aims to systematically evaluate the effects of mindfulness compared with conventional treatment on scores of the Hamilton Depression Scale (HAMD), Hamilton Anxiety Scale (HAMA), Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) in people with insomnia and anxiety-depressive symptoms. Methods Articles published before October 2022 were searched from seven databases and included in randomized controlled trials (RCTs) to evaluate mindfulness therapy. The assessment tool of Cochrane bias risk was used to evaluate the methodological quality of the literature. The main outcome indicators were HAMD and HAMA scores, and the secondary outcome indicators were SDS and SAS scores. Results Ten randomized controlled trials including 1,058 subjects were systematically evaluated and meta-analyzed in this study. In the main outcome indicators, there was a significant difference between mindfulness therapy and conventional treatment in reducing HAMD score (MD: −3.67, 95% CI: −5.22–2.11, p < 0.01) and HAMA score (MD: −3.23, 95% CI: −3.90–2.57, p < 0.01). In the secondary outcome indicators, mindfulness therapy also showed a significant difference in reducing SDS scores (MD: −6.49, 95% CI: −6.86–6.11, p < 0.01) and SAS scores (MD: −7.97, 95% CI: −9.68–6.27, p < 0.01) compared with conventional treatment. Conclusion For the people with insomnia, anxiety and depression, the use of conventional treatment with the addition of 4–12 weeks of mindfulness treatment can significantly improve anxiety and depression symptoms of patients. This is a new diagnosis and treatment idea recommended for insomniacs with or without anxiety and depression symptoms. Due to the methodological defects in the included study and the limited sample size of this paper, more well-designed randomized controlled trials are needed for verification.